Analisisi Kesulitan Pembelajaran Matematika Siswa Kelas VI SDN Purutrejo 1 Kota Pasuruan - Ayunina, Qurrotul; Lestari, Andika Setyo Budi; Fuat, Fuat (Indo-MathEdu Intellectuals Journal, 2024)
Students' learning difficulties in mathematics need to be considered from various aspects including teachers, students, and parents. Some students think that mathematics is a very difficult subject, especially for some students at SDN Purutrejo 1 Pasuruan City. This study aims to determine the characteristics of mathematics learning difficulties in elementary school students, as well as efforts that can overcome mathematics learning difficulties. This study uses a qualitative approach with a case study design. Participants in this study were mathematics teachers and six grade VI students who were selected based on teacher suggestions. Data collection techniques used observation, interviews, and documentation. The results of the analysis of this study are to determine the characteristics of mathematics learning difficulties, understand different formulas and what to do first, both internal and external factors, overcome difficulties when learning mathematics with effort. Internal factors are students' lack of interest and motivation in learning mathematics, and external factors are students' learning strategies, learning equipment, home environment, environment. Efforts that teachers can make include seeking college counseling and academic advice, as well as efforts that parents can make to motivate children and support their learning